PENGARUH KUALITAS PRODUK DAN LABEL HALAL TERHADAP KEPUTUSAN PEMBELIAN PRODUK (Study Kasus Pada Mahasiswa IAIN Salatiga) - Hifzhan Frima Thousani (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2021)
This study aims to determine the effect of product quality and halal label on Wardah cosmetic purchasing decisions. In this study, primary data was used by distributing questionnaires. The sample size in this study was 100 respondents who were consumers of wardah products. This study uses explanatory research that uses a quantitative approach with validity test, reliability test, t test and F test. The results of this study indicate that the purchasing decision of wardah cosmetics is significantly positively influenced by product quality and halal labels. The recommendation from this research is that the company must maintain good quality and continue to improve it to maintain the loyalty of loyal consumers of Wardah cosmetic products.